Omalizumab and long-term quality of life outcomes in patients with moderate-to-severe allergic asthma: a systematic review. (April 2019) - Colombo, Giorgio Lorenzo; Di Matteo, Sergio; Martinotti, Chiara; Oselin, Martina; Valentino, Maria Chiara; Bruno, Giacomo Matteo; Pitotti, Claudia; Menzella, Francesco
Background: Asthma is a highly prevalent chronic inflammatory airways disease, with a considerable impact on quality of life (QoL). To express the effects of asthma on patients' subjective experience, patient-reported outcomes (PROs) represent an important instrument. The asthma QoL questionnaire (AQLQ) is one of the main PROs among these. Materials and methods: To identify long-term asthma-related QoL outcomes associated with omalizumab therapy in patients with moderate-to-severe asthma, we developed a systematic review according to the PRISMA guidelines. Published real-world effectiveness studies of adults or adolescents (12 years or older) with moderate-to-severe allergic asthma treated with omalizumab for at least 48 weeks were reviewed. Sources used were Medline ( PubMed ), the Cochrane Library and Google Scholar up to February 2018. In addition, a cross-referencing search was conducted to complete the revision. Results: A total of 255 potential papers were identified in the first search through the database. After full-text viewing, eight articles were finally included in the review. We summarized the results according to the study design, patient baseline characteristics and effectiveness outcomes assessed by AQLQ score results: variation from baseline to the end of study. Results confirmed the long-term benefits of omalizumab as an add-on therapy in patients with uncontrolled moderate-to-severe allergic asthma. Since there is a lot of evidence on omalizumab effectiveness, we aimed to focus on how a therapy can change patient's QoL in a long time period. Data showed long-term effects of omalizumab treatment on subjective (PROs) and objective (lung function, corticosteroid use, hospitalizations, asthma exacerbation) effectiveness measures. Conclusion: Studies included in our review were observational trials that, due to their design, present a potential risk of selection bias in the patients included. Beyond this limit, the evaluation of QoL using the AQLQ showed a clear increase over time, following both 48 weeks and 9 years of observation, where QoL improvements still were significant over baseline values.